Kinerja Portal Struktur Gedung Tahan Gempa dengan Sistem Ganda Menggunakan Metode Pushover Analysis - Septian, N.; Turuallo, G.; Sulendra, I.K. (Civil Engineering Department, Tadulako University, 2022)
Buildings damages due to earthquakes generally happen because designs of the buildings do not consider earthquake resistance aspects and do not fulfil the technical standards of earthquake resistant buildings. The structure designed in this work was a seven-storey office building, with a symmetrical design plan. The earthquake-resisting system used was dual system with special moment resisting frame (SMRF) and special shear wall for reinforced concrete. The materials used in this design were concrete with compressive strength of f 'c = 30 MPa, Plain Steel Bars Grade 24 (fy = 235 MPa), and Deformed Steel Bars Grade 40 (fy = 390 MPa). The calculation structural elements results gave: the size of main beams of 40 x 60 cm2, with reinforcement varying from 4D22 to 12D22 in the support area and from 3D22 to 5D22 in the midspan area; secondary beams with the size of 25 x 40 cm2, with reinforcement of 2D22 both in the support area and midspan area; the size of columns were 95 x 95 cm2, with reinforcement varying from 20D25 to 28D25; a 30 cm thick of shear walls reinforced with 2D22-175 mm (in x-axis) and 2D22-125 mm (in y-axis); 12 cm thick slabs reinforced with Ø12-200 mm . For the tie beams with the size of 40 x 55 cm2, had reinforcement varying from 2D22 to 4D22 in the support area and from 3D22 to 5D22 in the midspan area. Pushover analysis results in a maximum total drift of 0,00425 which means the performance level of the structure is Immediate Occupancy